CONTRACTUAL DELEGATION OF SOVEREIGNTY IN SUPRANATIONAL ENTITIES - Zavalna, Zhanna; Starynskyi, Mykola (Global Prosperity, 2021)
The article analyses the agreement basis for state sovereignty as established and implemented in the European Union. The research aims to study the agreement-based regulation used by the EU Member States to create a stable position of Ukraine on its way to becoming a member of the European Union. The research allowed finding out that the member states do not transfer their powers in their economic and social fields but only delegate them. The analysis of the treaties concerning the establishment and functioning of the European Union proves the existence of specific organisational and legal intervention measures that the countries agree to when joining the treaty union. The agreement-based rearrangement of powers between the EU and its member states lets the latter obtain their special legal personalities regarding the conclusion of agreements among themselves and at the same time preserve complete economic sovereignty in their relations with the countries that are not member states of the EU. When joining the European Union, its member states voluntarily and on a negotiable basis agree to certain restrictions and prohibitions binding in their economy. Furthermore, the EC Treaty provides for the improved protection of interests for the economic community as compared with the protection of national interests of the member states though it is not excluded that the latter can be taken into consideration when adopting the national laws of a member state to the EU legislation.